Detection and measurement of digital imbalances on a local scale related to the mechanism for production and distribution of cultural information - Rodríguez-Ortega, Nuria (My University, 2018)
The creative economy has been defined as the role played by artistic creation, creative sectors and cultural institutions in the articulation of new production models that catalyze the generation of wealth, quality of life and social welfare (European Commission, 2010 UNESCO, 2013, Unctad, 2010). According to this understanding, it seems evident that the mechanisms for the production and distribution of cultural information are closely related to the possibilities of its promotion and development, since they are able to mobilize the flow of people and communities to certain locations , to highlight the distributed cultural heritage and so on (Casacuberta et al., 2008). Therefore, our starting point is the assumption that the digital practices associated with the production and distribution of cultural information are part of the systemic and structural factors that must be taken into consideration when evaluating the possibilities of certain territories to project their creative potential and add value to their own cultural richness.
Detección y medición de desequilibrios digitales a escala local relacionados con los mecanismos de producción y distribución de información cultural
Detection and Measurement of Digital Imbalances on a Local Scale Related to the Mechanism for Production and Distribution of Cultural Information Nuria Rodríguez - Ortega (nro@uma.es), University of Mála ga, Spain Digital Humanities Annual Conference ́2018, Mexico . Books of abstracts . (Ciudad de México, 26 - 29 de junio de 2018). Eds. Jonathan Girón Palau e Isabel Galina Russell Ciudad de México: Colegio de México, UNAM, Red de Humanidades Digitales HD, 2018. ISBN: 978 - 0 - 911221 - 62 - 6, pp . 268 - 270. Online abstract available at: https://dh2018.adho.org/deteccion-y-medicion-de-desequilibrios-digitales-a-escala-local-relacionados-con-los-mecanismos-de-produccion-y-distribucion-de-informacion-cultural/
Keywords: Digital Art History; Digital Humanities; Data Analysis; Creative Economy; Art Exhibitions